Comparative analysis of shear behavior and mechanism of concrete beams with strip-shaped CFRP or conventional steel stirrups - Lu, Yao; Li, Weiwen; Zhou, Yingwu; Mansour, Walid; Zheng, Kailun; Wang, Peng; Ke, Linyuwen; Yu, Jing (Case Studies in Construction Materials, 2024)
Carbon fiber-reinforced polymer (CFRP) is attractive to serve as reinforcements for concrete structures under harsh environmental conditions. Previous studies show that strip-shaped CFRP stirrups are satisfactory to replace conventional steel stirrups for concrete beams under shear, but the shear resistance mechanism of the strip-shape CFRP stirrups is not well understood. To fill this research gap, this study conducts a comparative analysis to examine the effects of different types of stirrups (CFRP or steel) on the distribution of shear cracks and the variation in shear resistance components of concrete beams with varying shear span-depth (a/d) ratios. A digital image correlation (DIC) technique is employed to capture the shear crack development of the beams. The results demonstrate that the strip-shaped CFRP stirrups (designed based on the principle of equal stiffness with steel stirrups) effectively restrain the propagation of individual shear crack, particularly at a large shear span (a/d=3.5). This enhanced crack restraint leads to a notable reduction in crack width and a significant increase in shear resistance component by 37.5% in the ultimate state when the strip-shaped CFRP stirrups are employed, compared to their steel stirrup counterparts at the same a/d ratio. These findings can facilitate the design and applications of concrete beams with CFRP stirrups.